The Acute Effects of External Compression With Blood Flow Restriction on Maximal Strength and Strength-Endurance Performance of the Upper Limbs - Wilk, Michal; Krzysztofik, Michal; Filip, Aleksandra; Lockie, Robert G.; Zajac, Adam (Frontiers in Physiology, 2020)
The main goal of the present study was to evaluate the acute effects external compression with blood flow restriction (BFR) at 100 and 150% of full arterial occlusion pressure (AOP) on maximal strength and strength-endurance performance during the bench press exercise (BP). The study included 12 strength-trained male subjects (age = 23.2 ± 2.66 years; body mass = 75.3 ± 6.33 kg; height = 179.1 ± 3.82 cm), experienced in resistance training (5.7 ± 2.93years). During the experimental sessions in an randomized crossover design, the subjects performed a 1 repetition maximum (1RM) test and 3 sets of the BP using 60%1RM to failure with 3 different conditions: without BFR (NO-BFR); BFR with a pressure of 100%AOP (BFR100) and BFR with a pressure of 150%AOP (BFR150). The differences between the NO-BFR, BFR100, BFR150 conditions were examined using repeated measures ANOVA. The ANOVA indicated significant main effect for condition in 1RM, number of performed repetitions (REP) and time under tension (TUT) (p<0.01). Post hoc analyses for the main effect indicated significant increases in 1RM (p<0.01; 95.00 ± 15.37 vs 91.87 ± 15.99), REP (p<0.01; 17.56 ± 3.36 vs 15.67 ± 5.24) and TUT (p<0.01; 32.89 ± 6.40 vs 28.72 ± 6.18) for the BFR150 condition compared to NO-BFR. Furthermore significant increases in REP (p=0.03; 17.56 ± 3.36 vs 16.47 ± 4.01) and TUT (p=0.03; 32.89 ± 6.40 vs 30.00 ± 6.45) were observed for the BFR150 condition compared to the BFR100. The results of the present study indicate that high external compression increases maximal strength evaluated by the 1RM test, as well as endurance performance during three sets of the bench press exercise.